PERLINDUNGAN HAK CIPTA TERHADAP BATIK SEMARANG - Adi Suliantoro; Fitika Andraini; RR Dewi Handayani UN; Alif Candra Pratama (Jurnal Ilmiah Dinamika Hukum, 2016)
Intellectual Property Rights for Batik Semarang still not as expected. Though the existence of Batik Semarang has existed since the Dutch colonial era around the 19th century and the motive is not inferior to other batik. Supposedly IPR can be applied to protect Batik Semarang, especially is The Copyright. The issue is What is the Copyright can be used to protect and preserve Batik Semarang? If ok what is the problem of it that can not apply its IPR, especially for Copyright. The conclusions is: Copyright can be applied to art / motive. The obstacles are the traditional motif is already a Public Domain, shall have the novelty of novation, Batik Semarang is not widely known and less desirable both from employers and community batik Semarang. Suggested communities often use Batik Semarang by requiring students to use Batik Semarang.